Optimization of a wind powered desalination and pumped hydro storage system. (1st September 2016) - Segurado, R.; Madeira, J.F.A.; Costa, M.; Duić, N.; Carvalho, M.G.
Highlights: Operational strategy and sizing optimization of an integrated power and water supply system. Multiobjective optimization using the Direct Multisearch method. Significant increase in RES production of total electricity production is feasible. Significant cost and CO2 emissions reductions are achievable. Abstract: The penetration of intermittent renewable energy sources, for instances wind power, in the power system of isolated islands is limited, even when there is large potential. The wind power that cannot be directly injected in the power grid is usually curtailed. In addition, some islands need to desalinate seawater to produce fresh water, increasing the pressure on the power system, because desalination needs electricity. Nevertheless, the water scarcity problem of an island can be part of the solution of the problem of its integration of intermittent renewable energy sources. To tackle this issue, a system was proposed to use the excess wind power in desalination units and in a pumped hydro storage, resulting in an integrated power and water supply system that would minimize the wind power curtailed. This paper proposes a methodology to optimize the size and operational strategy of this wind powered desalination and pumped hydro storage system. The objective is to minimize the total annualized production costs, maximize the percentage of renewable energy sources in the total power production and minimize the wind power curtailed. To solve this optimization problem, a derivative free multiobjective optimization method (Direct MultiSearch) is used. This methodology is applied to the integrated power and water supply system proposed for the island of S. Vicente, in Cape Verde. The results show that the penetration of renewable energy sources can reach 84% with a 27% decrease of power and water production costs and 67% decrease of CO2 emissions, in relation to the values foreseen for 2020.